(untitled) (Diametros, 2020)
The standard account of elsewhere is that it is any place that isn’t here. In this paper I argue against this account by demonstrating that (given some plausible assumptions) it results in a contra-diction. In its place I offer a modified account of elsewhere; where a place can only be elsewhere if it is in the same type of space as here.